Urban density in sustainable and liveable towns ( sustainability ) - Tan, Jeffery Yong Sheng (2015)
Urbanization is a worldwide phenomenon with more than half of the world population living in cities and built-up areas now. With the increase of population in cities, urban planners increasingly look to public transit as the ideal solution to move its people. However, additional financial cost may be incurred by the city to sustain the transit system in the event of a lack in its demand. This project looks at the relationship between the cities’ population and the financial sustainability of the public transit. A methodology was proposed to determine if the population is able to financially sustain the public transit through a series of individual, changeable models and a grading system. The models were required to generate output of ridership and revenue based on the input of population information. The financial sustainability of the city is determined by comparing the revenue and current cost of operation of the public transit operators. Results on financial sustainability can be assessed through a grading system with C being the minimum. The methods that were developed were then tested using Singapore's population and transit system as a case study. Data were collected from the various agencies on the population, transit ridership and public transit revenue. The linear relationships between population and ridership, as well as, ridership and revenue were then determined. Comparing the public transit revenue with the operation cost, it was found that Singapore’s public transit scored a B grade in terms of financial sustainability. This means that the demand for public transit in Singapore is sufficient for the public transit operators to be sustainable without assistance from the government.